2019
DOI: 10.1017/s0950268819001997
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of genetic polymorphisms in CTLA-4 and IL-18 with viral hepatitis: evidence from a meta-analysis

Abstract: Relationship of genetic polymorphisms in cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) and interleukin-18 (IL-18) with susceptibility to viral hepatitis was already investigated by many association studies. The aim of this study was to more comprehensively analyse associations between genetic polymorphisms in CTLA-4/IL-18 and viral hepatitis by combing the results of all relevant association studies. We searched Pubmed, Embase, Web of Science and CNKI for eligible studies. We used Review Manager to comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Wang et al in a 10-year follow-up, reported a significant association of rs231775 genotype GG with the progression of chronic hepatitis B Virus (HBV) infection to cirrhosis and HCC [ 43 ]. The result of the meta-analysis performed by Yu et al revealed a significant association of rs231775 polymorphism in the recessive inheritance model with susceptibility to HBV, especially in East Asian patients [ 44 ]. Chen et al [ 45 ] and Gu et al (24) identified the +49A allele as a risk factor and the +49G allele as a protective factor against HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al in a 10-year follow-up, reported a significant association of rs231775 genotype GG with the progression of chronic hepatitis B Virus (HBV) infection to cirrhosis and HCC [ 43 ]. The result of the meta-analysis performed by Yu et al revealed a significant association of rs231775 polymorphism in the recessive inheritance model with susceptibility to HBV, especially in East Asian patients [ 44 ]. Chen et al [ 45 ] and Gu et al (24) identified the +49A allele as a risk factor and the +49G allele as a protective factor against HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to RA predisposition, increasing evidence on the association between IL-18 polymorphisms and other disease conditions has also been reported by systematic reviews and meta-analyses. The -607 C/A and/or -137 G/C polymorphisms in IL-18 may confer susceptibility to tuberculosis, especially in Asians [33]; inflammatory bowel disease, including both Crohn's disease and ulcerative colitis in Asians and Africans [34][35][36]; vasculitis [37] and systemic lupus erythematosus in Europeans and Asians [38]; Behcet's disease [39], various types of liver diseases [40,41], hepatitis B virus in East Asians and hepatitis C virus infection in South Asians [42] and Asian populations [43]; diabetic nephropathy in Asians [44]; allergic asthma and allergic dermatitis [45][46][47], Alzheimer's disease in Asians [48,49]; periodontitis [50], coronary artery disease in East Asians [51,52]; head and neck cancer risk, especially nasopharyngeal cancer, in Asian populations [53]; breast cancer in East Asians from China [54,55]; and prostate cancer in Asian and Caucasian populations [56]. IL-18 has been reported to be a potential clinical biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al performed a meta-analysis of the relationship between IL-18 gene polymorphisms and viral hepatitis. The results demonstrate that the IL-18 rs1946518 and IL-18 rs187238 polymorphisms may be associated with the susceptibility of East Asians to HBV [ 87 ]. In addition, serum IL-18 levels were significantly increased as HBV disease progressed to HCC compared with controls [ 88 ].…”
Section: Interleukin-18mentioning
confidence: 99%